“MRI Cooling System Analysis & Optimization: CFD, Temperature Control & Efficiency Enhancement” - Shinde, Sunil; Chougule, Sunil; Sanap, Vikas; Sandhan, Durgesh; Saravade, Aditya; Rasal, Mukta; Shah, Kushal; shirbavikar, Ketaki (International Journal of Membrane Science and Technology, 2023)
This paper presents a compressive analysis and optimization of a twisted heat tube exchanger for MRI cooling system. The objective of this study is to enhance the efficiency and temperature control of the system adhering to ASHRAE standards by altering the coolant inlet temperature from 18° C to 27°C & the hot inlet temperature from 75°C to 100°C. The research encompasses design modifications, thermal analysis of tubes with varying lengths (400mm,800mm,1200mm), CFD Analysis simulation to understand fluid behavior. By employing these analyses & optimizations, we aim to improve the overall performance & efficiency of the MRI cooling system. This work not only contributes to the field of heat exchangers & MRI Cooling but also provides valuable insights for HVAC world by replacement of refrigerant or conventional MRI cooling system.